Uncovering the Role of Professional Learning Community in Driving Teacher Innovation and Competency - Erni Triyanti; Ammang Latifa; Salasiah Ammade; Rafi’ah Nur; Siti Hajar Larekeng (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aims to examine the impact of teacher participation in Professional Learning Communities (PLCs) on the enhancement of teacher competencies in UPTD SMAN 2 Polewali. A quantitative approach was employed, using a Likert-scale questionnaire to measure the level of teacher engagement in PLCs and their professional competencies, including pedagogical, professional, social, and personal aspects. The findings reveal that active participation in PLCs significantly improves teachers' ability to adopt innovative and effective teaching strategies, manage classrooms, and engage in reflective practices. Moreover, PLCs provide a collaborative space for teachers to share experiences, address challenges, and develop joint solutions, ultimately fostering a culture of continuous improvement in educational quality. Despite these promising results, this study is limited to a specific local context, and the use of quantitative methods restricts the exploration of in-depth interactions within PLCs. Future research should incorporate mixed methods and expand to diverse regions to achieve broader generalizability and deeper insights.